2008
DOI: 10.1590/s0104-66322008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of caffeine, chlorogenic acids and lipids from green coffee beans using supercritical carbon dioxide and co-solvents

Abstract: The paper reports on experimental data on the extraction of caffeine, coffee oil and chlorogenic acids from green coffee beans using pure supercritical CO2 and supercritical CO2 modified with ethanol (5% w/w) and isopropyl alcohol (5% w/w) at 50 and 60ºC and 15.2 24.8 e 35.2 MPa. In this study extraction kinetics were obtained for all assays i.e. samples were collected at several time intervals for each solvent and mixed solvent. When pure CO2 and CO2-ethanol mixed solvent were used, an increase in pressure re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 33 publications
(36 reference statements)
2
39
0
10
Order By: Relevance
“…Caffeine is not recovered, but charcoal can be regenerated at 800°C. The main disadvantage of using organic solvents is the low selectivity and, as a consequence, other substances important for beverage quality may be removed from the beans [16]. A highly selective method of decaf production is achieved with supercritical CO 2 , developed by Kurt Zosel in the 1970's and licensed by Kaffee HAG and later by General Foods [169].…”
Section: How To Get Rid Of Caffeinementioning
confidence: 99%
“…Caffeine is not recovered, but charcoal can be regenerated at 800°C. The main disadvantage of using organic solvents is the low selectivity and, as a consequence, other substances important for beverage quality may be removed from the beans [16]. A highly selective method of decaf production is achieved with supercritical CO 2 , developed by Kurt Zosel in the 1970's and licensed by Kaffee HAG and later by General Foods [169].…”
Section: How To Get Rid Of Caffeinementioning
confidence: 99%
“…The supercritical fluid has properties such as high diffusivity, low viscosity and low surface tension, which gives it attractive characteristics as a solvent for the extraction of components from the solid matrix (Taylor, 1996). Advantages of the use of carbon dioxide under supercritical conditions are selectivity (Cardozo et al, 2007;Azevedo et al, 2008) and solubility (Brennecke and Eckert, 1989). Marongiu et al (2004) studied the CO 2 supercritical extraction of S. molle and indicated that increasing the CO 2 density permits the extraction of compounds of high molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Both caffeine and chlorogenic acid were quantified following the methodology described by Azevedo et al (2008). In the case of caffeine determination in husks, after the extraction of compounds from coffee pods, samples were filtered through a 0.20 µm-pore membrane and injected into an Ultra Efficiency Liquid Chromatography column (UPLC, LC-2010HT, Shimadzu, São Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%